Dry particle composition, ceramic tile with embossment color effect and preparation method of ceramic tile
Through the use of specific dry-grain compositions and adhesives, the problem of lack of relief effect on the surface of ceramic tiles is solved, and the visual and tactile and performance improvement of ceramic products is achieved, and the competitiveness of the products is improved.
Patent Information
- Application Number
- CN202411866165.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The surface of existing ceramic tiles lacks concave and convex relief effect, resulting in insufficient visual and tactile sensory improvement, and the homogeneity caused by inkjet printing technology seriously makes the product lose its competitiveness.
By providing a dry particle composition, including specific proportional combinations of medium and high temperature and low temperature dry particles, a ceramic product with a wide firing temperature is formed, combining a specific adhesive and protective glaze layer, ensuring significant relief effect on the surface of the ceramic product is achieved by a significant amount of time. , stable, and improve hardness, wear resistance, anti-slip and stain resistance.
It achieves significant relief effect on the surface of ceramic products, enhances visual and tactile experience, and improves product competitiveness, and has higher mass production stability and performance indicators.
Smart Images

Figure CN119320235A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of ceramic technology, and in particular to a dry particle composition, a ceramic tile with embossed color effect and a preparation method thereof. Background Art
[0002] With the application of inkjet printing technology in ceramic tile production, the surface decoration technology of ceramic wall and floor tiles has changed with each passing day. It is favored by many ceramic wall and floor tile manufacturers due to its high simulation, short pattern and color development cycle, fast change, and simple operation. However, it also brings serious drawbacks of homogeneity, making the products lose competitiveness. Moreover, the surface of the ceramic tiles formed by it is usually flat, without concave and convex relief effects. Therefore, it is necessary to develop a technology to make the surface of ceramic tiles have concave and convex relief effects, so as to enhance the visual and tactile senses of ceramic tiles and improve product competitiveness. Summary of the invention
[0003] Based on the defects of the prior art, the purpose of the present application is to provide a dry particle composition, a ceramic tile with embossed color effect and a preparation method thereof.
[0004] In order to achieve the above-mentioned object, in a first aspect, the present application provides a dry particle composition, comprising first dry particles and second dry particles, wherein the weight ratio of the first dry particles to the second dry particles is (3-11.5):1; The first dry particles include the following chemical components by mass percentage: SiO2 51%-58%, Al2O3 16%-18%, Fe2O3 0.01%-0.1%, MgO 0.5%-3.0%, CaO 6.0-10.0%, Na2O 1.0%-3.5%, K2O 3%-5.5%, V2O50-0.04%, BaO 3.0%-5.5%, SrO2.5%-5.5%, ZnO2.5%-5.5%, SO3 0.01%-0.05%, PbO 0.01%-0.05%, loss on ignition 0.03%-2.0%; The second dry particles include the following chemical components by mass percentage: SiO2 55%-65%, Al2O3 10%-12%, Fe2O3 0.05%-0.2%, TiO2 0.01-0.04%, MgO 0.5%-2.5%, CaO 8%-12%, Na2O 0.5%-2.5%, Mn3O40-0.04%, P2O50-0.03%, ZrO2 0.05%-0.15%, K2O 3.5%-6.0%, BaO 0.2%-2.0%, SrO 0.02%-0.2%, ZnO 8%-13%, SO3 0-0.04%, PbO 0-0.2%, and loss on ignition 0.02%-1.5%. The first dry particles are medium-high temperature dry particles, and the second dry particles are low-temperature dry particles. By compounding the specific first dry particles and the second dry particles in a specific ratio, the dry particle composition has a wider firing temperature, ensuring that the relief effect on the surface of the ceramic product is significant and stable, and the batch production stability is high; at the same time, the surface hardness, wear resistance, anti-slip performance, stain resistance and other properties of the ceramic product are greatly improved compared with the products with ordinary printing decoration, and the fingers feel warm, smooth and delicate, and slightly bumpy like original stone.
[0005] The weight ratio of the first dry particles to the second dry particles is (3-11.5):1, for example, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 11.5:1 or an interval formed by any two of the above.
[0006] Preferably, the dry granular composition satisfies: D10=30-60 mesh, D50=60-140 mesh, D90=140-200 mesh.
[0007] In a second aspect, the present application provides a ceramic tile, comprising a body layer, a glaze layer, an adhesive layer, a dry particle layer and a protective glaze layer stacked in sequence; wherein the dry particle layer is formed using the dry particle composition.
[0008] The adhesive used to prepare the adhesive layer can be an adhesive commonly used in the art. However, the bonding properties of these adhesives are relatively weak, and a higher application amount is required to make the dry particle composition firmly bonded to the surface glaze layer and not easy to fall off. At the same time, it is also necessary to dry after applying the protective glaze. If the protective glaze is not dried after application, but directly put into the kiln for firing, there will be too much water in the brick blank, and cracking and brick explosion will occur after firing, resulting in a high scrap rate of ceramic tiles and poor performance; drying after applying the protective glaze can avoid cracking, brick explosion and other phenomena after firing, but the drying process needs to be strictly controlled. If the temperature, humidity and other factors of the environment fluctuate due to weather reasons during the drying process, the drying effect will change, and cracking, brick explosion and other phenomena will also occur after firing.
[0009] Preferably, the adhesive used to prepare the adhesive layer includes the following chemical components by mass percentage: organic solvent 45%-65%, wollastonite 20%-41.5%, zinc oxide 3%-8%, dispersant 2%-12%, acrylic polymer 8%-20%, viscosity stabilizer 0.5%-2.5%. The adhesive is added with a specific content of acrylic polymer to give it adhesive properties, and at the same time adds a specific content of wollastonite and zinc oxide, wherein wollastonite can improve the adhesiveness of the adhesive, improve the fluidity of the adhesive, and has the advantages of water resistance, heat resistance, strong chemical stability, and low cost; zinc oxide has good thermal conductivity, can provide the thermal capacity of the adhesive, and can also improve the viscosity, durability and stability of the adhesive, and can cooperate with wollastonite to improve the adhesive properties of the adhesive. The adhesive has very strong bonding properties under the joint action of the above components. It can quickly adhere the dry particle composition to the glaze at a relatively low application amount, so that the glaze surface absorbs water quickly. Even if the protective glaze is not dried after application and is directly fired, the bricks are not prone to cracking, brick explosion, etc.
[0010] Compared with other silicates, such as sodium silicate, adding wollastonite to the adhesive can make the adhesion significantly better; compared with other oxides, such as magnesium oxide, calcium oxide, kaolin, phosphorus pentoxide, silicon dioxide, cerium oxide, praseodymium oxide, lanthanum oxide, etc., adding zinc oxide to the adhesive can make the adhesion significantly better.
[0011] Preferably, the amount of adhesive applied is 300-1000 g / m 2 The amount of the dry granular composition applied is 500-1500 g / m 2 When the amount of the binder and the amount of the dry granular composition applied are within the above specific ranges, the protective glaze is not dried and fired directly, and the bricks are not prone to cracking, brick explosion, etc.
[0012] Preferably, the organic solvent comprises at least one of fatty acid, isopropyl oleate and dihexyl adipate.
[0013] Preferably, the dispersant comprises paraformaldehyde.
[0014] Preferably, the viscosity stabilizer includes at least one of epoxy resin, polyvinyl butyral, sodium polyacrylate, sodium carboxymethyl cellulose, BYKJET-9131 (BYK), BYKJET-9132 (BYK), and BYKJET-9133 (BYK).
[0015] Preferably, the protective glaze layer is colorful, and the slurry used to prepare the protective glaze layer includes the following chemical components by mass percentage: 0.5%-2% blue dry particles, 1%-5% red dry particles, 0.1%-1.5% black dry particles, 50%-70% suspending agent, 20%-35% fine powder dry particles, and 5%-15% transparent protective glaze; wherein, The blue dry particles include the following chemical components by mass percentage: SiO2 48%-53%, Al2O3 17%-20%, Fe2O3 0.1%-0.3%, TiO2 0.05%-0.15%, MgO 0.2%-1.0%, CaO 13%-17%, Na2O 1.5%-4.5%, Mn3O4 0.03%-0.15%, P2O5 0.05%-0.15%, ZrO2 0.1%-1.0%, K2O 0.5%-2.0%, BaO 0.01%-0.06%, SrO 1%-3%, ZnO 3%-5.5%, SO3 0.01%-0.1%, PbO 0.01%-0.05%, Co3O42.5%-4.5%, Cr2O30.01%-0.06%, ignition loss 0.05%-1.5%; The red dry granules include the following chemical components by mass percentage: SiO2 49%-54%, Al2O3 14%-17%, Fe2O3 0.1%-0.8%, TiO2 0.02%-0.15%, MgO 0.5%-2.5%, CaO 3%-5.5%, Na2O 1.5%-4.0%, Mn3O40-0.04%, P2O5 0.01%-0.15%, ZrO2 7.5%-12%, K2O 2.5%-5.5%, BaO 0.05%-0.2%, SrO 3%-6%, ZnO 5%-8%, SO3 0.1%-0.5%, PbO 0.02%-0.15%, CdO 0.1%-0.5%, Cr2O3 0.01%-0.1%, HfO2 0.1%-0.4%, ignition loss 0.05%-2.5%; The black dry particles include the following chemical components by mass percentage: SiO2 45%-51%, Al2O3 14.5%-16.5%, Fe2O3 0.3%-0.6%, TiO2 0.1%-0.4%, MgO 0.5%-2.5%, CaO 4%-7.5%, Na2O 3%-5.5%, Mn3O4 0.2%-0.9%, P2O5 0.05%-0.3%, ZrO2 0.01%-0.05%, K2O 1.5%-3.5%, BaO 0.05%-0.3%, SrO3.5%-5.5%, ZnO 4%-7%, SO3 0.01%-0.05%, PbO 0.04%-0.15%, Co3O4 1%-3%, Cr2O3 1%-3%, NiO 0.4%-0.9%, CuO0-0.08%, ignition reduction 2.5%-5%; The fine powder and dry particles include the following chemical components by mass percentage: SiO2 51%-56%, Al2O3 16%-18.5%, Fe2O3 0.01%-0.15%, TiO2 0-0.05%, MgO 0.5%-2.5%, CaO 6%-9%, Na2O 1%-3%, P2O5 0.01%-0.05%, ZrO2 0.03%-0.15%, K2O 3%-5.5%, BaO 3%-6%, SrO3%-6%, ZnO 2.5%-5.5%, PbO 0.01%-0.08%, V2O 50-0.08%, loss on ignition 2.5%-5.5%; The transparent protective glaze comprises the following chemical components by mass percentage: SiO2 46%-51%, Al2O3 17.5%-29.5%, Fe2O3 0.1%-0.2%, TiO2 0.01%-0.08%, MgO 3.5%-5.5%, CaO 1.5%-3.5%, Na2O 2.5%-4.5%, Mn3O4 0.01%-0.05%, P2O5 0.01%-0.08%, SO3 0.01%-0.08%, V2O5 0.01%-0.08%, ZrO2 0-0.04%, K2O 2%-4%, BaO 8.5%-11%, SrO 0.01%-0.1%, ZnO 3.5%-5.5%, ignition loss 3.5%-6.5%; The suspending agent comprises an acrylate polymer and a propylene glycol block copolymer, and the weight ratio of the acrylate polymer to the propylene glycol block copolymer is (10-13): (6-10).
[0016] When the slurry used to prepare the protective glaze layer adopts the above formula, the surface of the ceramic tile produced is colorful, it will emit a glittering light under the light, and the pattern is not prone to smudging, and it feels delicate.
[0017] The protective glaze layer may also be transparent. In some embodiments, the protective glaze layer includes the following chemical components by mass percentage: SiO2 46%-51%, Al2O3 17.5%-29.5%, Fe2O3 0.1%-0.2%, TiO2 0.01%-0.08%, MgO 3.5%-5.5%, CaO 1.5%-3.5%, Na2O 2.5%-4.5%, Mn3O4 0.01%-0.05%, P2O5 0.01%-0.08%, SO3 0.01%-0.08%, V2O5 0.01%-0.08%, ZrO2 0-0.04%, K2O 2%-4%, BaO 8.5%-11%, SrO 0.01%-0.1%, ZnO 3.5%-5.5%, ignition loss 3.5%-6.5%. In other embodiments, the protective glaze layer comprises the following chemical components in mass percentage: SiO2 50%-51%, TiO2 0.1%-0.2%, Al2O3 20%-21%, Fe2O3 0.1%-0.2%, MgO 2.5%-3%, CaO 6.5%-7%, Na2O 1.5%-2%, K2O 2%-3%, P2O5 0.1%-0.2%, SrO3%-3.5%, ZrO2 0.03-0.05%, HfO2 0.01%-0.03%, BaO 3%-3.5%, ZnO 5.8%-6.2%, and loss on ignition 1.5%-2%.
[0018] The slurry used to prepare the protective glaze layer may or may not contain any additives. For example, in some embodiments, water, sodium carboxymethyl cellulose and a water reducing agent are added to the slurry used to prepare the protective glaze layer, wherein the amount of water added is 5% to 10% of the weight of the slurry, the viscosity modifier is 0.1% to 0.15%, and the water reducing agent is 0.25% to 0.35%, wherein the viscosity modifier may be sodium carboxymethyl cellulose, etc., and the water reducing agent may be sodium tripolyphosphate, etc.
[0019] Preferably, the glaze layer comprises the following chemical components in mass percentage: SiO2 50%-60%, Al2O3 19%-22%, Fe2O3 0.05%-0.4%, TiO2 0.05%-0.3%, MgO 0.2%-1.5%, CaO 2.0%-4.5%, Na2O 2.0%-5.0%, Mn3O40-0.04%, P2O5 0.05%-0.5%, SO3 0.01%-0.1%, ZrO2 4.0%-7.0%, K2O 1.5%-3.5%, BaO 0.5%-3.5%, SrO0-1.0%, ZnO 2.0-4.0%, and loss on ignition 1.5%-3.5%.
[0020] In a third aspect, the present application provides a method for preparing ceramic tiles, comprising the following steps: pressing brick blanks, drying, applying glaze, coating adhesive, adhering the dry particle composition at the location where the adhesive is applied, blowing away the unadhered dry particle composition, spraying protective glaze, firing, polishing, and grinding edges to obtain ceramic tiles.
[0021] Preferably, when applying the glaze, the slurry used satisfies: the residue on a 325-mesh sieve is 0.4wt.%-0.7wt.%, the specific gravity is 1.85-1.92g / mL, and the flow rate is 32-42s / 100mL.
[0022] Preferably, when spraying the protective glaze, the slurry used satisfies: the residue on a 325-mesh sieve is 2wt.%-8wt.%, the specific gravity is 1.35-1.55g / mL, and the flow rate is 25-30s / 100mL.
[0023] Preferably, the polishing step is as follows: first, at a pressure of 1.0-1.5 MPa, use 4 groups of 240 mesh fiber modules for fine polishing for 30-50 seconds and 4 groups of 240 mesh plastic silicon carbide grinding brushes for fine polishing for 20-40 seconds, then use 8 groups of 240 mesh fiber modules for fine polishing for 40-50 seconds and 5 groups of 240 mesh plastic silicon carbide grinding brushes for fine polishing for 20-40 seconds. The above polishing process is used to make the relief effect of the ceramic tile more significant and three-dimensional, and to improve its stain resistance, skid resistance, wear resistance, flexural strength and other properties.
[0024] Compared with the prior art, the beneficial effects of the present application are as follows: the present application compounded the specific first dry particles and the second dry particles in a specific ratio, so that the obtained dry particle composition has a wider firing temperature, ensuring that the surface relief effect of the ceramic product is significant and stable, and the batch production stability is high; at the same time, the surface hardness, wear resistance, anti-slip performance, stain resistance and other properties of the ceramic product are greatly improved compared with the products with ordinary printed decorations, the fingers touch the warm and smooth, and the surface is slightly concave and convex like the original stone, which is superior to the ordinary wall and floor tile products in terms of vision and touch, and greatly improves the competitiveness of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a photo of the ceramic tile of Test Example 1; Figure 2 This is a photo of the ceramic tile of Test Example 8; Figure 3 This is a photo of the ceramic tile of Test Example 9; Figure 4 In Test Example 10, adhesive 6 was used and the application amount was 1000 g / m 2 A photo of the dry granular composition not adhering to the substrate after being sucked away by a fan; Figure 5 In Test Example 10, adhesive 6 was used and the application amount was 1500 g / m 2This is a photo of the dry granular composition that was not adhered being sucked away by a fan. DETAILED DESCRIPTION
[0026] In order to better illustrate the purpose, technical solutions and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0027] The propylene glycol block copolymer used below is L64 from Foshan Hengrong New Materials Co., Ltd.; the acrylate polymer is acrylic acid (ester) / C10-30 alkyl acrylate cross-linked polymer from Foshan Shunlong New Materials Co., Ltd.
[0028] Test Example 1 A method for preparing a ceramic tile with a relief color effect is provided, comprising the following steps: (1) pressing a green body, and drying the green body at 190° C. for 40 minutes to obtain a dried green body; (2) The entire upper surface of the dried blank is glazed with a cup-shaped glaze, wherein the slurry used meets the following requirements: the residue on a 325-mesh sieve is 0.5 wt.%, the specific gravity is 1.86 g / mL, the flow rate is 38 s / 100 mL, and the glaze spraying amount is 600 g / m 2 , and the glaze formed by the slurry used includes the following chemical compositions by mass percentage: SiO2 56%, Al2O3 20.64%, Fe2O3 0.21%, TiO2 0.18%, MgO 0.33%, CaO 3.61%, Na2O 3.57%, Mn3O4 0.01%, P2O5 0.24%, SO3 0.04%, ZrO2 5.57%, K2O 2.49%, BaO 1.42%, SrO 0.01%, ZnO 3.38%, ignition loss 2.3%; (3) Printing ink to form prints; (4) Design the relief pattern using Photoshop software to form a texture inkjet file with a specific adhesive position effect. Print the adhesive according to the design, with an adhesive application amount of 800g / m 2The adhesive includes the following chemical components by mass percentage: 54% organic solvent, 25% wollastonite, 4% zinc oxide, 7% dispersant, 8% acrylic polymer, and 2% viscosity stabilizer, wherein the organic solvent is fatty acid, the dispersant is paraformaldehyde, and the viscosity stabilizer is epoxy resin; (5) Using a dry granulator to apply the dry granular composition at the location where the adhesive is applied, the amount of dry granular composition applied is 1000 g / m 2 , using a fan to suck away the dry granular composition that is not adhered, wherein the particle size of the dry granular composition satisfies D10=50 mesh, D50=100 mesh, and D90=160 mesh; The dry particle composition is compounded by first dry particles and second dry particles, and the mass ratio of the first dry particles to the second dry particles is 4.33:1; The first dry granules include the following chemical components by mass percentage: SiO2 54.52%, Al2O3 17.34%, Fe2O3 0.03%, MgO 1.73%, CaO 7.94%, Na2O 2.03%, K2O 4.33%, V2O5 0.01%, BaO 4.37%, SrO 3.92%, ZnO 3.61%, SO3 0.04%, PbO 0.04%, loss on ignition 0.09%; The second dry granules include the following chemical components by mass percentage: SiO2 59.58%, Al2O3 11.30%, Fe2O3 0.12%, TiO2 0.02%, MgO 1.22%, CaO 10.74%, Na2O 1.37%, Mn3O4 0.01%, P2O5 0.01%, ZrO2 0.09%, K2O 4.4%, BaO 0.8%, SrO 0.06%, ZnO 10.11%, SO3 0.01%, PbO 0.11%, loss on ignition 0.05%; (6) Spraying colored dry granule protective glaze, the slurry flow rate is 26s / 100mL, the specific gravity is 1.35 g / mL, the glaze amount is 250g / m², and the slurry used includes the following chemical components by mass percentage: blue dry granules 1%, red dry granules 3%, black dry granules 1%, suspending agent 60%, fine powder dry granules 22%, transparent protective glaze 13%, of which: The suspending agent includes an acrylate polymer and a propylene glycol block copolymer, and the mass ratio of the acrylate polymer to the propylene glycol block copolymer is 12:8; The blue dry granules include the following chemical components by mass percentage: SiO250.44%, Al2O319.18%, Fe2O30.2%, TiO20.1%, MgO 0.41%, CaO 15.09%, Na2O 3.22%, Mn3O40.09%, P2O50.1%, ZrO20.38%, K2O1.06%, BaO 0.03%, SrO2.09%, ZnO4.34%, SO30.04%, PbO 0.04%, Co3O43.01%, Cr2O30.02%, loss on ignition 0.16%; Red dry granules include the following chemical components by mass percentage: SiO2 51.82%, Al2O3 15.03%, Fe2O3 0.42%, TiO2 0.08%, MgO 1.12%, CaO 4.15%, Na2O 2.49%, Mn3O4 0.01%, P2O5 0.08%, ZrO2 9.10%, K2O 3.42%, BaO 0.10%, SrO 4.58%, ZnO 6.47%, SO3 0.24%, PbO 0.08%, CdO 0.35%, Cr2O3 0.05%, HfO2 0.24%, loss on ignition 0.17%; The black dry granules include the following chemical components by mass percentage: SiO2 49.76%, Al2O3 15.67%, Fe2O3 0.42%, TiO2 0.23%, MgO 1.40%, CaO 5.97%, Na2O 4.44%, Mn3O4 0.57%, P2O5 0.13%, ZrO2 0.02%, K2O 2.26%, BaO 0.14%, SrO 4.32%, ZnO 5.75%, SO3 0.03%, PbO 0.09%, Co3O4 2.03%, Cr2O3 2.17%, NiO 0.59%, CuO 0.03%, loss on ignition 3.98%; The fine powder and dry particles include the following chemical components by mass percentage: SiO251.61%, Al2O317.44%, Fe2O30.07%, TiO20.01%, MgO 1.87%, CaO 7.19%, Na2O 2.11%, P2O50.02%, ZrO20.07%, K2O4.43%, BaO 4.28%, SrO3.96%, ZnO3.72%, PbO 0.04%, V2O50.03%, loss on ignition 3.15%; The transparent protective glaze includes the following chemical components by mass percentage: SiO2 48.37%, Al2O3 18.22%, Fe2O3 0.16%, TiO2 0.05%, MgO 4.55%, CaO 2.5%, Na2O 3.38%, Mn3O4 0.02%, P2O5 0.05%, SO3 0.04%, V2O5 0.05%, ZrO2 0.01%, K2O 3.09%, BaO 9.65%, SrO 0.05%, ZnO 4.38%, ignition loss 5.43%; (7) Firing, temperature 1200°C, firing cycle 55 minutes; (8) After firing, the semi-finished ceramic tiles are firstly polished by 4 groups of 240-mesh fiber modules for 40 seconds and 4 groups of 240-mesh plastic silicon carbide grinding brushes for 30 seconds under a pressure of 1.0 MPa, then polished by 8 groups of 240-mesh fiber modules for 50 seconds and 5 groups of 240-mesh plastic silicon carbide grinding brushes for 30 seconds, and then edge-polished to obtain ceramic tiles.
[0029] Test Example 2 Provided is a method for preparing a ceramic tile with a relief color effect, which is different from Experimental Example 1 in that the mass ratio of the first dry particles to the second dry particles is 8.25:1.
[0030] Test Example 3 Provided is a method for preparing a ceramic tile with a relief color effect, which is different from Experimental Example 1 in that the mass ratio of the first dry particles to the second dry particles is 11.25:1.
[0031] Test Example 4 Provided is a method for preparing a ceramic tile with a relief color effect, which differs from Experimental Example 1 in that the first dry particles include the following chemical components by mass percentage: SiO2 57.29%, Al2O3 16.02%, Fe2O3 0.01%, MgO 0.52%, CaO 6.35%, Na2O 1.07%, K2O 5.41%, V2O50, BaO 5.39%, SrO 5.32%, ZnO 2.57%, SO3 0.01%, PbO 0.01%, and loss on ignition 0.03%; The second dry granules include the following chemical components by mass percentage: SiO2 55.01%, Al2O3 10.13%, Fe2O3 0.05%, TiO2 0.01%, MgO 0.54%, CaO 11.89%, Na2O 2.47%, Mn3O40, P2O50, ZrO2 0.05%, K2O 5.98%, BaO 0.23%, SrO 0.02%, ZnO 12.95%, SO30, PbO0, loss on ignition 0.67%; The particle size of the dry granular composition satisfies D10=30 mesh, D50=60 mesh, and D90=140 mesh; The slurry used for spraying colored dry granule protective glaze includes the following chemical components by mass percentage: blue dry granule 0.5%, red dry granule 1%, black dry granule 0.1%, suspending agent 66%, fine powder dry granule 20%, transparent protective glaze 12.4%; The suspending agent includes an acrylate polymer and a propylene glycol block copolymer, and the mass ratio of the acrylate polymer to the propylene glycol block copolymer is 10:10; The blue dry granules include the following chemical components by mass percentage: SiO2 52.70%, Al2O3 17.21%, Fe2O3 0.12%, TiO2 0.05%, MgO 0.23%, CaO 16.85%, Na2O 1.54%, Mn3O4 0.03%, P2O5 0.05%, ZrO2 0.12%, K2O 0.57%, BaO 0.01%, SrO2.97%, ZnO 3.05%, SO3 0.01%, PbO 0.01%, Co3O4 4.42%, Cr2O3 0.01%, loss on ignition 0.05%; Red dry granules include the following chemical components by mass percentage: SiO2 49.07%, Al2O3 16.01%, Fe2O3 0.76%, TiO2 0.15%, MgO 2.24%, CaO 4.81%, Na2O 3.06%, Mn3O4 0.04%, P2O5 0.12%, ZrO2 7.52%, K2O 4.81%, BaO 0.18%, SrO 3.03%, ZnO 5.06%, SO3 0.39%, PbO 0.15%, CdO 0.43%, Cr2O3 0.09%, HfO2 0.36%, loss on ignition 1.72%; The black dry granules include the following chemical components by mass percentage: SiO246.01%, Al2O316.48%, Fe2O30.57%, TiO20.38%, MgO 2.49%, CaO 4.21%, Na2O 5.36%, Mn3O40.84%, P2O50.24%, ZrO20.05%, K2O3.49%, BaO 0.25%, SrO5.41%, ZnO4.45%, SO30.05%, PbO 0.15%, Co3O42.97%, Cr2O32.92%, NiO0.84%, CuO 0.08%, loss on ignition 2.76%; The fine powder and dry particles include the following chemical components by mass percentage: SiO251.02%, Al2O317.54%, Fe2O30.12%, TiO20.05%, MgO 2.06%, CaO6.02%, Na2O 2.38%, P2O50.05%, ZrO20.11%, K2O5.03%, BaO3.02%, SrO5.01%, ZnO2.51%, PbO 0.08%, V2O50.08%, loss on ignition 4.92%; The transparent protective glaze includes the following chemical components in mass percentage: SiO2 46.01%, Al2O3 23.06%, Fe2O3 0.18%, TiO2 0.08%, MgO 3.51%, CaO 2.95%, Na2O 3.36%, Mn3O4 0.05%, P2O5 0.08%, SO3 0.07%, V2O5 0.08%, ZrO2 0.04%, K2O 2.02%, BaO 8.51%, SrO 0.09%, ZnO 4.05%, and ignition loss 5.86%.
[0032] Test Example 5 A method for preparing a ceramic tile with a relief color effect is provided, which is different from that of Experimental Example 1 in that the formula of the first dry particles is different, as follows: The first dry granules include the following chemical components by mass percentage: SiO2 51.02%, Al2O3 17.77%, Fe2O3 0.09%, MgO 2.87%, CaO 9.32%, Na2O 3.18%, K2O 3.11%, V2O 5 0.04%, BaO 3.03%, SrO 2.52%, ZnO 5.11%, SO3 0.04%, PbO 0.05%, loss on ignition 1.85%; The second dry granules include the following chemical components by mass percentage: SiO2 62.78%, Al2O3 11.56%, Fe2O3 0.18%, TiO2 0.04%, MgO 2.32%, CaO 8.11%, Na2O 0.57%, Mn3O4 0.04%, P2O5 0.03%, ZrO2 0.15%, K2O 3.52%, BaO 1.83%, SrO 0.19%, ZnO 8.05%, SO3 0.04%, PbO 0.18%, loss on ignition 0.41%; the particle size of the dry granule composition satisfies D10=60 mesh, D50=140 mesh, and D90=200 mesh; The slurry used for spraying colored dry granule protective glaze includes the following chemical components by mass percentage: 2% blue dry granule, 5% red dry granule, 1.5% black dry granule, 50% suspending agent, 35% fine powder dry granule, and 6.5% transparent protective glaze; The suspending agent includes an acrylate polymer and a propylene glycol block copolymer, and the mass ratio of the acrylate polymer to the propylene glycol block copolymer is 13:6; The blue dry granules include the following chemical components by mass percentage: SiO2 48.09%, Al2O3 19.69%, Fe2O3 0.28%, TiO2 0.15%, MgO 0.97%, CaO 13.05%, Na2O 4.05%, Mn3O4 0.15%, P2O5 0.15%, ZrO2 0.93%, K2O 1.89%, BaO 0.06%, SrO 1.13%, ZnO 5.33%, SO3 0.09%, PbO 0.05%, Co3O4 2.56%, Cr2O3 0.06%, loss on ignition 1.32%; Red dry granules include the following chemical components by mass percentage: SiO2 52.81%, Al2O3 14.03%, Fe2O3 0.11%, TiO2 0.02%, MgO 0.54%, CaO 3.16%, Na2O 1.52%, Mn3O40, P2O5 0.01%, ZrO2 11.23%, K2O 2.55%, BaO 0.05%, SrO 5.89%, ZnO 7.59%, SO3 0.12%, PbO 0.02%, CdO 0.17%, Cr2O3 0.01%, HfO2 0.12%, loss on ignition 0.05%; The black dry granules include the following chemical components by mass percentage: SiO250.98%, Al2O314.99%, Fe2O30.33%, TiO20.14%, MgO 0.56%, CaO 7.43%, Na2O 3.80%, Mn3O40.25%, P2O50.05%, ZrO20.01%, K2O1.97%, BaO 0.05%, SrO3.98%, ZnO6.94%, SO30.01%, PbO 0.04%, Co3O41.52%, Cr2O31.46%, NiO0.52%, CuO 0, loss on ignition 4.97%; The fine powder and dry particles include the following chemical components by mass percentage: SiO2 55.17%, Al2O3 16.02%, Fe2O3 0.01%, TiO20, MgO 0.52%, CaO 8.48%, Na2O 1.04%, P2O5 0.01%, ZrO2 0.03%, K2O 3.02%, BaO 5.06%, SrO 3.01%, ZnO 5.09%, PbO 0.01%, V2O50, loss on ignition 2.53%; The transparent protective glaze includes the following chemical components in mass percentage: SiO250.78%, Al2O317.53%, Fe2O30.15%, TiO20.01%, MgO 5.42%, CaO1.56%, Na2O 2.54%, Mn3O40.01%, P2O50.01%, SO30.01%, V2O50.01%, ZrO20, K2O3.99%, BaO10.88%, SrO0.01%, ZnO3.52%, and loss on ignition 3.57%.
[0033] Test Example 6 Provided is a method for preparing a ceramic tile with a relief color effect, which is different from Experimental Example 1 in that the mass ratio of the first dry particles to the second dry particles is 2.5:1.
[0034] Test Example 7 Provided is a method for preparing a ceramic tile with a relief color effect, which is different from Experimental Example 1 in that the mass ratio of the first dry particles to the second dry particles is 12.5:1.
[0035] Test Example 8 A method for preparing a ceramic tile with a relief color effect is provided, which is different from Experimental Example 1 in that the first dry particles include the following chemical components by mass percentage: SiO251.43%, Al2O320.38%, Fe2O30.03%, MgO 1.72%, CaO 7.93%, Na2O 2.05%, K2O4.35%, V2O50.01%, BaO 4.38%, SrO3.92%, ZnO3.63%, SO30.04%, PbO0.04%, ignition loss 0.09%; Test Example 9 A method for preparing a ceramic tile with a relief color effect is provided, which is different from Experimental Example 1 in that the second dry particles include the following chemical components by mass percentage: The second dry granules include the following chemical components by mass percentage: SiO2 54.53%, Al2O3 16.30%, Fe2O3 0.12%, TiO2 0.02%, MgO 1.23%, CaO 10.75%, Na2O 1.38%, Mn3O4 0.01%, P2O5 0.01%, ZrO2 0.09%, K2O 4.41%, BaO 0.79%, SrO 0.06%, ZnO 10.13%, SO3 0.01%, PbO 0.12%, loss on ignition 0.04%; The following properties of the ceramic tiles obtained in the above test examples were measured: Static friction coefficient determination: refer to GB / T 4100-2006. A static friction coefficient of 0.9 or above indicates anti-slip. Stain resistance test: refer to GB / T 3810.14-2006, the test pollutants include: light oil containing chrome green, light oil containing red pollutants, iodine solution and olive oil. If the stain resistance level reaches 5, it means good stain resistance; Flexural strength determination: refer to GB / T 4100-2015; Determination of wear resistance: Refer to "GB / T 3810.2-2016". A wear resistance grade of 4 indicates good wear resistance.
[0036] Relief height difference: The ceramic tile obtained in the above test example is laminated with the upper surface of a common ceramic tile (Xin Mingzhu, GF-DV157510-555), and the gap between them is tested to obtain the relief height difference. If the relief height difference is within the range of 2.0~3.5mm, the relief is significant, beautiful, and has a good effect. Glaze effect: 10 testers are selected to observe and touch the relief effect to see if it is three-dimensional and has a convex feeling of the mold, and to observe whether it is dazzling and whether the color position effect obviously absorbs dirt. If the ceramic tile does not crack or explode, and after the dry particles that are not adhered are blown away with a hair dryer during the preparation process, there is no obvious lack of dry particles at the location of the designed relief, the score will be scored. The more delicate and warm the touch is, and the stronger the convex feeling of the mold, the higher the score. On the contrary, the rougher or less obvious the relief, the lower the score. The average score is calculated, with 9 to 10 points for excellent, 7 to 8 points for qualified, and less than 7 points for unqualified; if the ceramic tile appears and / or explodes and / or the dry particles that are not adhered are blown away with a hair dryer during the preparation process, there is obvious lack of dry particles at the location of the designed relief, no score is required.
[0037] The test results are shown in Table 1.
[0038] Table 1 From the above data, it can be seen that the ceramic tiles in test examples 1 to 5 have good stain resistance, anti-slip and wear resistance, such as stain resistance of level 5, static friction coefficient of above 0.92, wear resistance of level 4, and high flexural strength of above 43MPa, strong color development ability, excellent glaze effect, and good relief effect. The relief height difference is in the range of 2.0-3.5㎜, and the color effect is good.
[0039] In Test Example 6, the mass ratio of the first dry particles to the second dry particles is relatively low, resulting in a high proportion of low-temperature dry particles in the dry particle composition. During the firing process, the degree of melting of the dry particle composition is too high, resulting in an insignificant relief effect, unstable relief collapse, too bright and dazzling relief positions, poor anti-slip properties, and too low a firing temperature at the collapsed position, resulting in poor wear resistance.
[0040] In Test Example 7, the mass ratio of the first dry particles to the second dry particles is relatively high, resulting in a high proportion of high-temperature dry particles in the dry particle composition, which leads to the opening of adsorption pores, more serious dirt absorption, rough relief and low height difference, and poor anti-slip properties.
[0041] In Test Example 8, the aluminum oxide content in the first dry particles is relatively high, and the required sintering temperature is high, so although the relief is strong, it is rough and has serious dirt absorption.
[0042] In Test Example 9, the alumina content in the second dry particles is low, and the required sintering temperature is low, which makes the relief collapse unstable, the relief position is too bright and dazzling, the color effect is average, and the wear resistance is poor.
[0043] Depend on Figure 1 It can be seen that the ceramic tile obtained in Experimental Example 1 has a good three-dimensional relief effect and an obvious color position effect.
[0044] Depend on Figure 2 It can be seen that although the ceramic tile obtained in Test Example 8 has good relief and color effects, it has obvious dirt absorption.
[0045] Depend on Figure 3 It can be seen that the ceramic tile relief obtained in Test Example 9 collapsed unstably, and the relief position was too bright and glaring, and the color effect was average.
[0046] Test Example 10 Based on Test Example 1, the effect of adhesive on the relief effect of ceramic tiles was studied. The composition of the adhesive used is shown in Table 2, wherein the organic solvent is fatty acid, the dispersant is paraformaldehyde, the viscosity stabilizer is epoxy resin, the other silicate is sodium silicate (water glass), and the other oxide is calcium oxide: Table 2 According to the preparation method of ceramic tiles in Experimental Example 1, adhesives 1 to 10 are used to prepare ceramic tiles. The application amount of the adhesive is shown in Table 3. When the application amount of the adhesive is 1000 g / m 2 When the amount of adhesive applied is greater than 1000g / m 2 When spraying the colored dry particle protective glaze, it was dried at 120°C and then fired. The other treatments were the same as those in Experimental Example 1. The performance test was then carried out according to the above method, and the results are shown in Table 3.
[0047] Table 3 As shown in Table 3, when the adhesive includes the following chemical components by mass percentage: organic solvent 45%-65%, wollastonite 20%-41.5%, zinc oxide 3%-8%, dispersant 2%-12%, acrylic polymer 8%-20%, viscosity stabilizer 0.5%-2.5%, its application amount is low, such as 300-1000g / m 2 Within the range, the protective glaze is applied without drying and is directly fired, and the bricks do not crack or explode, and the glaze effect is excellent, and the relief color effect is good; while the adhesive 6-10 does not contain wollastonite, or contains excessive wollastonite, or does not contain zinc oxide, or other silicates are used to replace wollastonite, or other oxides are used to replace zinc oxide, resulting in relatively weak bonding performance, requiring a higher application amount and drying before firing after applying the protective glaze to avoid cracking or exploded bricks.
[0048] from Figure 4 and 5 It can be seen that when the amount of adhesive 6 applied is low, the adhesion to the dry particles is weak, resulting in obvious loss of dry particles at the position of the designed relief after the unadhered dry particles are blown away with a hair dryer; when the amount of adhesive 6 applied is large, the adhesion to the dry particles is strong, and after the unadhered dry particles are blown away with a hair dryer, no obvious loss of dry particles occurs at the position of the designed relief.
[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A dry granular composition, characterized in that: The invention comprises first dry particles and second dry particles, wherein the weight ratio of the first dry particles to the second dry particles is (3-11.5):1; The first dry particles include the following chemical components by mass percentage: SiO2 51%-58%, Al2O3 16%-18%, Fe2O3 0.01%-0.1%, MgO 0.5%-3.0%, CaO 6.0-10.0%, Na2O 1.0%-3.5%, K2O 3%-5.5%, V2O 50-0.04%, BaO 3.0%-5.5%, SrO2.5%-5.5%, ZnO2.5%-5.5%, SO3 0.01%-0.05%, PbO 0.01%-0.05%, loss on ignition 0.03%-2.0%; The second dry particles include the following chemical components by mass percentage: SiO2 55%-65%, Al2O3 10%-12%, Fe2O3 0.05%-0.2%, TiO2 0.01-0.04%, MgO 0.5%-2.5%, CaO 8%-12%, Na2O 0.5%-2.5%, Mn3O40-0.04%, P2O50-0.03%, ZrO2 0.05%-0.15%, K2O 3.5%-6.0%, BaO 0.2%-2.0%, SrO 0.02%-0.2%, ZnO 8%-13%, SO3 0-0.04%, PbO 0-0.2%, and loss on ignition 0.02%-1.5%.
2. The dry granular composition according to claim 1, characterized in that The dry granular composition meets the following requirements: D10=30-60 mesh, D50=60-140 mesh, and D90=140-200 mesh.
3. A ceramic tile, characterized in that: The invention comprises a body layer, a glaze layer, an adhesive layer, a dry particle layer and a protective glaze layer which are stacked in sequence; wherein the dry particle layer is formed by using the dry particle composition according to claim 1.
4. The ceramic tile according to claim 3, characterized in that: The adhesive used to prepare the adhesive layer includes the following chemical components by mass percentage: 45%-65% organic solvent, 20%-41.5% wollastonite, 3%-8% zinc oxide, 2%-12% dispersant, 8%-20% acrylic polymer, and 0.5%-2.5% viscosity stabilizer.
5. The ceramic tile according to claim 4, characterized in that: The organic solvent comprises at least one of fatty acid, isopropyl oleate and dihexyl adipate; and / or The dispersant includes paraformaldehyde; The viscosity stabilizer includes at least one of epoxy resin, polyvinyl butyral, sodium polyacrylate, sodium carboxymethyl cellulose, BYKJET-9131, BYKJET-9132, and BYKJET-9133.
6. The ceramic tile according to claim 4, characterized in that: The amount of adhesive applied is 300-1000g / m 2 The amount of the dry granular composition applied is 500-1500 g / m 2 .
7. The ceramic tile according to claim 3, characterized in that: The protective glaze layer is colorful, and the slurry used to prepare the protective glaze layer includes the following chemical components by mass percentage: 0.5%-2% blue dry particles, 1%-5% red dry particles, 0.1%-1.5% black dry particles, 50%-70% suspending agent, 20%-35% fine powder dry particles, and 5%-15% transparent protective glaze; wherein, The blue dry particles include the following chemical components by mass percentage: SiO2 48%-53%, Al2O3 17%-20%, Fe2O3 0.1%-0.3%, TiO2 0.05%-0.15%, MgO 0.2%-1.0%, CaO 13%-17%, Na2O 1.5%-4.5%, Mn3O4 0.03%-0.15%, P2O5 0.05%-0.15%, ZrO2 0.1%-1.0%, K2O 0.5%-2.0%, BaO 0.01%-0.06%, SrO1%-3%, ZnO3%-5.5%, SO30.01%-0.1%, PbO0.01%-0.05%, Co3O42.5%-4.5%, Cr2O30.01%-0.06%, ignition loss 0.05%-1.5%; The red dry granules include the following chemical components by mass percentage: SiO2 49%-54%, Al2O3 14%-17%, Fe2O3 0.1%-0.8%, TiO2 0.02%-0.15%, MgO 0.5%-2.5%, CaO 3%-5.5%, Na2O 1.5%-4.0%, Mn3O40-0.04%, P2O5 0.01%-0.15%, ZrO2 7.5%-12%, K2O 2.5%-5.5%, BaO 0.05%-0.2%, SrO 3%-6%, ZnO 5%-8%, SO3 0.1%-0.5%, PbO 0.02%-0.15%, CdO0.1%-0.5%, Cr2O30.01%-0.1%, HfO20.1%-0.4%, ignition loss0.05%-2.5%; The black dry particles include the following chemical components by mass percentage: SiO2 45%-51%, Al2O3 14.5%-16.5%, Fe2O3 0.3%-0.6%, TiO2 0.1%-0.4%, MgO 0.5%-2.5%, CaO 4%-7.5%, Na2O 3%-5.5%, Mn3O4 0.2%-0.9%, P2O5 0.05%-0.3%, ZrO2 0.01%-0.05%, K2O 1.5%-3.5%, BaO 0.05%-0.3%, SrO 3.5%-5.5%, ZnO 4%-7%, SO3 0.01%-0.05%, PbO 0.04%-0.15%, Co3O4 1%-3%, Cr2O3 1%-3%, NiO 0.4%-0.9%, CuO0-0.08%, ignition reduction 2.5%-5%; The fine powder and dry particles include the following chemical components by mass percentage: SiO2 51%-56%, Al2O3 16%-18.5%, Fe2O3 0.01%-0.15%, TiO2 0-0.05%, MgO 0.5%-2.5%, CaO 6%-9%, Na2O 1%-3%, P2O5 0.01%-0.05%, ZrO2 0.03%-0.15%, K2O 3%-5.5%, BaO 3%-6%, SrO3%-6%, ZnO 2.5%-5.5%, PbO 0.01%-0.08%, V2O 50-0.08%, loss on ignition 2.5%-5.5%; The transparent protective glaze comprises the following chemical components by mass percentage: SiO2 46%-51%, Al2O3 17.5%-29.5%, Fe2O3 0.1%-0.2%, TiO2 0.01%-0.08%, MgO 3.5%-5.5%, CaO 1.5%-3.5%, Na2O 2.5%-4.5%, Mn3O4 0.01%-0.05%, P2O5 0.01%-0.08%, SO3 0.01%-0.08%, V2O5 0.01%-0.08%, ZrO2 0-0.04%, K2O 2%-4%, BaO 8.5%-11%, SrO 0.01%-0.1%, ZnO 3.5%-5.5%, ignition loss 3.5%-6.5%; The suspending agent comprises an acrylate polymer and a propylene glycol block copolymer, and the weight ratio of the acrylate polymer to the propylene glycol block copolymer is (10-13): (6-10).
8. The ceramic tile according to claim 3, characterized in that: The glaze layer includes the following chemical components in mass percentage: SiO2 50%-60%, Al2O3 19%-22%, Fe2O3 0.05%-0.4%, TiO2 0.05%-0.3%, MgO 0.2%-1.5%, CaO 2.0%-4.5%, Na2O 2.0%-5.0%, Mn3O4 0-0.04%, P2O5 0.05%-0.5%, SO3 0.01%-0.1%, ZrO2 4.0%-7.0%, K2O 1.5%-3.5%, BaO 0.5%-3.5%, SrO0-1.0%, ZnO 2.0-4.0%, and loss on ignition 1.5%-3.5%.
9. The method for preparing a ceramic tile according to claim 6, characterized in that: The following steps are involved: The green bricks are pressed, dried, glazed, coated with adhesive, the dry granular composition is adhered to the position where the adhesive is applied, the unadhered dry granular composition is blown away, protective glaze is sprayed, fired, polished, and edged to obtain ceramic bricks.
10. The method for preparing a ceramic tile according to claim 9, characterized in that: When applying the glaze, the slurry used meets the following requirements: the residue on a 325-mesh sieve is 0.4wt.%-0.7wt.%, the specific gravity is 1.85-1.92g / mL, and the flow rate is 32-42s / 100mL; When spraying the protective glaze, the slurry used meets the following requirements: the residue on a 325-mesh sieve is 2wt.%-8wt.%, the specific gravity is 1.35-1.55g / mL, and the flow rate is 25-30s / 100mL; The polishing steps are as follows: first, at a pressure of 1.0-1.5 MPa, use 4 groups of 240-mesh fiber modules for fine polishing for 30-50 seconds and 4 groups of 240-mesh plastic silicon carbide grinding brushes for fine polishing for 20-40 seconds, then use 8 groups of 240-mesh fiber modules for fine polishing for 40-50 seconds and 5 groups of 240-mesh plastic silicon carbide grinding brushes for fine polishing for 20-40 seconds.
Citation Information
Patent Citations
Full-polished glaze and preparation method thereof, and black ink-jet ceramic tile and manufacturing method thereof
CN110683766A
Dry granular glaze for soft polished brick and application of dry granular glaze
CN110862231A
Treatment method capable of realizing glimmering surface of fine dry-grained rock plate
CN114057397A
Reticulated ceramic tile and preparation method thereof
CN116354745A
Ceramic tile with high flatness and glossiness and super-thick upper and lower embossments and preparation method of ceramic tile
CN117105700A
Cited By
Ceramic tile with colorful effect and preparation method thereof
CN119490303A